(untitled) (LIS TODAY, 2023)
This study explores the impact of Information and Communication Technology (ICT) on librarians employed at five specifically chosen university libraries in Nepal. The research used a structured questionnaire as a data collection tool. The research engaged all five university librarians, and all distributed questionnaires were completed and returned. The study’s findings indicate that while university librarians demonstrated competence in fundamental ICT applications, there is a recognized need for additional knowledge acquisition to achieve proficiency in specific ICT tools. Moreover, all surveyed librarians strongly agreed that integrating ICT applications contributes positively to the stature of libraries.